Sequence analysis of control region (D-Loop) of mtDNA from five Vietnamese individuals - Huệ Huỳnh Thị Thu; Yến Hoàng Thị Thu; Tôn Nguyễn Đăng; Hiền Lê Thị Thu; Cường Nguyễn Đinh; Chi, Phan Văn; Hải Nông Văn (Vietnam Journal of Biotechnology, 2008)
Journal of Biotechnology 3(1): 15-22, 2005